Analysis of Electrospun Nylon 6 Nanofibrous Membrane as Filters (Journal of Fiber Bioengineering and Informatics, 2018)
In this work, nylon 6 was firstly dissolved in 98% formic acid with the concentration of 13wt%, and then electrospun to obtain nanofibrous membranes. The morphology of the electrospun nylon 6 nanofibrous membranes was observed by scanning electron microscopy (SEM), the filtration efficiency and the mechanical properties were also examined. The results show that the average diameter of electrospun nylon 6 fiber was 217 nm, the surface average pore diameter was 234 nm, the thickness was 31 to 60
Keywords: Electrospinnin; nanofibers; mechanical properties; nylon 6; filtration performance